PRAGMA-COGNITIVE APPLICATION OF LINGUO-SEMATIC MODELS AND THEIR APPLICATION IN SCIENCE - Nurmatova Sadbarkhan Erkinovna (Journals Park Publishing, 2023)
The article describes the pragma-cognitive implementation of linguosematic models and their characteristics, the opinions of scientists, the concepts of cognitive linguistics, and information about cognitive pragmas.
Keywords: linguistics, pragma, scientific view, cognitive, science, linguistics, lexicon, system, unity, law.